Status and Genetic Character of Atlantic Sturgeon in the Satilla River, Georgia. Issue 1 (23rd December 2015) - Fritts, Mark W.; Grunwald, Cheryl; Wirgin, Isaac; King, Tim L.; Peterson, Douglas L.
Abstract: The Atlantic Sturgeon Acipenser oxyrinchus oxyrinchus is an important component of biodiversity along the Atlantic coast of North America, but most populations have been decimated by habitat degradation and chronic overfishing. Historically, spawning populations existed in all major Atlantic coast rivers from the St. Lawrence River, Quebec, to the St. Johns River, Florida, but fisheries surveys conducted in the past two decades suggest that several populations at the southern extent of this range are now extirpated or have declined to remnant status. Our objective was to assess the abundance and genetic character of Atlantic Sturgeon in the Satilla River, Georgia. Using entanglement gears, we expended over 2, 800 h of sampling effort and captured a total of 193 Atlantic Sturgeon in tidally influenced reaches of the river during 2008–2010. Of the 157 fish that were collected in 2010, 72 were identified as river‐resident juveniles (ages 0–1). Genetic analyses of a subset ( n = 61) of these juveniles revealed (1) depauperate levels of mitochondrial DNA (mtDNA) haplotype diversity and (2) the presence of large family units based on microsatellite DNA multilocus genotypes, collectively suggesting that very few parents produced the 2008 year‐class. The mtDNA and microsatellite analyses both indicated that juveniles in the Satilla River population were genetically distinct from other populations in the South Atlantic Distinct Population Segment. Atlantic Sturgeon life history characteristics and the present results suggest that sampled juveniles from the 2008 year‐class were the offspring of a small remnant pool of Satilla River adults; however, a full description of the population's genetic character and origin will require additional juvenile samples from future year‐classes.